Enabling Genome Editing for Enhanced Agricultural Sustainability - Keiper, Felicity; Atanassova, Ana (Frontiers in Genome Editing, 2022)
Agricultural sustainability encompasses environmental, social, and economic aspects, all of which are continually shifting due changing environmental pressures and societal expectations. A range of strategies are required to address these challenges, and these include the use of innovation and adoption of the best available practices and technologies. Advances in biotechnologies, including genome editing, and their application in plant breeding and research are expected to provide a range of benefits that contribute to all aspects of agricultural sustainability. However, adoption of these technologies needs to be supported by proportionate, coherent, forward-looking, and adaptable policies and regulatory approaches. In this Perspective, we reflect on the regulatory challenges associated with commercializing a transgenic crop, and developments thus far in providing regulatory clarity for genome edited crops. We aim to demonstrate that much remains to be done to shift towards a more proportionate and enabling approach before the potential benefits of genome edited crops can be realized. The implications of precautionary and disproportionate regulation are also discussed.